La Marseillaise à l’École... ou pas ! Enseigner la France face à l’ethnicisation - François Durpaire (Recherches en Éducation)
Article 2 of the framework law of 23 April 2005 recalled that "in addition to imparting knowledge, the Nation sets as first mission school to share with students the values of Republic. "The education code recalls that civic education" necessarily involves learning the national anthem and its history. "What can we say of practical teaching of the Marseillaise, compared for example with the United States where teaches Pledge of Allegiance? What does this teaching of the national anthem or not it say of to the school transmission of a "membership citizenship" which was one of its original missions? Beyond that, is teaching the nation one of the solutions envisaged to build Common in a school where different identities coexist.citizenship and environment (personal social and health education), immigration and ethnicity